Reading and its relationships among attitude, motivation, and comprehension achievement in upper secondary school students - Tisa, Fatimah; Sofendi, Sofendi; Eryansyah, Eryansyah (JEES (Journal of English Educators Society), 2021)
Reading is essential in every subject. Reading also has a relationship with the students' achievement. This study is aimed to investigate whether or not there is (1) a significant correlation between reading attitude and reading comprehension achievement, (2) a significant correlation between reading motivation and reading comprehension achievement, (3) a significant correlation between reading attitude and reading motivation, and (4) any correlation between predictor variables and the criterion variable. The study was a correlational study with Pearson-product moment correlation. The sample of this study were 95 eleventh graders of upper secondary school. Cluster random sampling technique is used in this study. Questionnaires of reading attitude, reading motivation, and reading comprehension tests are given. The questionnaire result reveals that the reading attitude was negative, and reading motivation is medium. Furthermore, the results show that reading attitude and reading comprehension has a significant correlation. Reading motivation and reading comprehension also has a significant correlation. The roles of students, parents and teachers must work suitably in order to construct the positive reading atmosphere, thus they could achieve the better achievement in reading even for all subjects. HIGHLIGHTS: The supports from family in motivating the children to be a good reader could build the positive attitude toward reading. Reading motivation can lead to the improvement in language learning performance. The learners who tend to read simple English texts can be said as the learners who were lacking English reading experiences.